Generasi Z, Pustakawan, dan Vita Activa Kepustakawanan - Kamil, Rusdan; Laksmi (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2023)
ABSTRACT Currently, generation Z has become one of the active groups in the world of librarianship. Vita Activa, or active life, refers to human life actively engaged with the material world, including social, cultural, and political affairs. In his book “Cerita Tentang Pustakawan dan Kepustakawanan” (CTPK), Sudarsono argues that librarianship should go beyond administrative tasks in collecting and storing books. This research employs Critical Discourse Analysis (CDA) method developed by Fairclough, with a focus on examining the content of librarianship in the book